Review of adaptations of U.S. Commercial Fisheries in response to the COVID ‐19 pandemic using the Resist ‐ Accept ‐ Direct (RAD) framework - Sarah Lindley Smith; Samantha Cook; Abigail Golden; Mia Aiko Iwane; Danika Kleiber; Kirsten M. Leong; Anthony Mastitski; Laurie Richmond; Marysia Szymkowiak; Sarah Wise (Fisheries Management and Ecology, 2022)
The COVID‐19 pandemic transformed social and economic systems globally, including fisheries systems. Decreases in seafood demand, supply chain disruptions, and public safety regulations required numerous adaptations to maintain the livelihoods and social resilience of fishing communities. Surveys, interviews, and focus groups were undertaken to assess impacts from and adaptive responses to the pandemic in commercial fisheries in five U.S. regions: the Northeast, California, Alaska, the U.S. Caribbean, and the Pacific Islands. Fishery adaptation strategies were categorized using the Resist–Accept–Direct (RAD) framework, a novel application to understand social transformation in a social‐ecological system in response to a disturbance. A number of innovations emerged, or were facilitated, that could improve the fisheries' resilience to future disruptions. Fishers with diversified options and strategic flexibility generally fared better, i.e., had fewer disruptions to their livelihoods. Using the RAD framework to identify adaptation strategies from fishery system actors highlights opportunities for improving resilience of fisheries social‐ecological systems to future stressors.